2022
DOI: 10.7717/peerj.12911
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance and virulence profiles of Enterobacterales isolated from two-finger and three-finger sloths (Choloepus hoffmanni and Bradypus variegatus) of Costa Rica

Abstract: Background Wildlife has been recently recognized as an environmental reservoir for antimicrobial resistance (AMR). However, less information on this topic is available in animals released back into the wild after rehabilitation in wildlife facilities, compared with studies performed exclusively in captive or free-ranging wildlife. This study aimed to evaluate the potential influence of captivity and/or treatment while in captivity of wild sloths on the AMR and virulence profiles of sloths’ Enterobacterales. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Nevertheless, harbour porpoise samples were retrieved mainly from the Baltic Sea and harbour seal samples mainly from the North Sea, which might indicate a species difference rather than a spatial one. Furthermore, due to the delay in sample processing, it is possible that the number of E. coli was underestimated, although it has been shown that samples collected at larger distances and longer processing periods allow the isolation and characterization of Gram-negative bacteria [ 91 , 92 , 93 ]. Nevertheless, it cannot be excluded that the delay in sample processing could also be the reason for the observed lack of resistant E. coli in the sampled fishes.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, harbour porpoise samples were retrieved mainly from the Baltic Sea and harbour seal samples mainly from the North Sea, which might indicate a species difference rather than a spatial one. Furthermore, due to the delay in sample processing, it is possible that the number of E. coli was underestimated, although it has been shown that samples collected at larger distances and longer processing periods allow the isolation and characterization of Gram-negative bacteria [ 91 , 92 , 93 ]. Nevertheless, it cannot be excluded that the delay in sample processing could also be the reason for the observed lack of resistant E. coli in the sampled fishes.…”
Section: Discussionmentioning
confidence: 99%
“…Isolates were characterized considering their macroscopic morphology on ChromID ® ESBL according to the manufacturer’s instructions (bioMérieux, Linda-a-Velha, Portugal), Gram staining, lactose-fermentation capability on MacConkey agar (Oxoid, Hampshire, UK), and oxidase production. Biochemical identification was performed by IMViC testing [ 97 ] or, in case of inconclusive result by IMViC, API 20E (bioMérieux, Linda-a-Velha, Portugal) galleries were used according to manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Swabs were inoculated in Brain Heart Infusion broth and incubated for 48 h at 37 • C [30], after which bacterial suspensions were spread onto MacConkey agar (VWR, Leuven, Belgium) surface, and incubated at 37 • C for 48 h. After incubation, four lactosefermenting colonies, each surrounded by a halo of bile salt precipitation, were selected for further identification [31]. Isolates were tested using oxidase reagent swabs (VWR, Leuven, Belgium) and characterized by Gram staining.…”
Section: Bacterial Isolation and Identificationmentioning
confidence: 99%
“…The isolates' virulence profiles were assessed using specific media [29,31]. Results were read after incubation at 37 • C for 24 to 48 h, except for gelatinase activity.…”
Section: Isolates' Virulence Profilesmentioning
confidence: 99%
See 1 more Smart Citation